Art-making in practice: achieving optimal creativity during the conceptual design process - Lininger, Taylor (Kansas State University, 2016)
There can be no design product without a design process to achieve it; how we design is just as important as what we design. If landscape architects engage creative activities at work, they may be able to achieve flow, "an optimal and positive state of mind during which key individuals are highly motivated and engrossed" (Fullagar, Knight, and Sovern 2013, 236). Individuals experiencing flow find themselves in situations with challenge/skill balance, intrinsic motivation, and empowering self-confidence. The methods used for this master's project and report evaluated three art-making techniques in terms of the flow state and the design solutions they inspired. Watercolor, printmaking, and digital drawing were each incorporated into three simple design projects and filmed for peer-review. Fellow landscape architecture students reviewed segments of the film and completed a survey to measure the author's flow state. Additionally, they provided a critique of the art-making processes based on their perceptions of the filmed design processes and resulting design solutions. The peer assessment, accompanied with the author's self-reflection of art-making as ideation, provide insights into creativity and "good" design. Art - as concept, craft, and communication - are integral and evident in every part of the project. The findings show how design processes that include different art-making media affect and facilitate a flow state that leads to responsive design concepts. Landscape architects should incorporate art-making into their professional practice as a means of facilitating creativity without spending excessive amounts of time or resources in the conceptual stage of a design process.
Keywords: Landscape architecture; Art-making; Design process; Flow; Creativity; Ideation